Evaluation of the antidiarrheal and antioxidant properties of Justicia hypocrateriformis. (September 2014) - Agbor, Gabriel A.; Longo, Frida; Makong, Estelle A.; Tarkang, Protus Arrey
Abstract Content: Justicia hypocrateriformis Vahl (Acanthaceae) is used as an herbal remedy for diarrhea in Cameroon folk medicine. Objective: This study evaluates the antidiarrheal and antioxidant properties of the aqueous extract of J. hypocrateriformis (JH). Materials and methods: Preliminary phytochemical screening and an acute toxicity testing of the extract were carried out. The antidiarrheal activity of JH extract (100, 250, and 500 mg/kg) was assessed at curative and preventive levels in castor oil-induced diarrhea in mice. The antioxidant activity was measured by ferric reducing antioxidant power (FRAP), total phenolic content, and radical scavenging activity. Results: A high lethal dose (LD50) of 14.35 g/kg obtained in acute toxicity implies the extract is not toxic. Phytochemical screening revealed the presence of phenols, tannins, flavonoids, saponins, anthraquinones, and anthocyanins. JH showed a significant protection against castor oil-induced diarrhea as evidenced by a decrease in the number of defecation and wet stool. JH (100–500 mg/kg, p.o.) produced a non-significant dose-dependent decrease in castor oil-induced intestinal transit in the preventive study. In the curative and in healthy mice study, the decrease was only significant at 500 mg/kg. JH possessed a radical scavenging activity with an IC50 of 9.93 mg/ml compared to 4.90 mg/ml for catechin. JH FRAP of 2703.77 ± 0 mg/g (catechin equiv) and phenolic concentration of 14 169.99 ± 612.39 mg/g (catechin equiv) were also obtained. Conclusion: Justicia hypocrateriformis extract possesses antidiarrheal activity supported by its antioxidant potential and phytochemical constituents.